Comparing sexual risks and patterns of alcohol and drug use between injection drug users (IDUs) and non-IDUs who report sexual partnerships with IDUs in St. Petersburg, Russia - Verevochkin Sergei; Krasnoselskikh Tatiana V; Toussova Olga V; White Edward; Abdala Nadia; Kozlov Andrei P; Heimer Robert (BMC, 2010)
Abstract Background To date, the great majority of Russian HIV infections have been diagnosed among IDUs and concerns about the potential for a sexual transmission of HIV beyond the IDU population have increased. This study investigated differences in the prevalence of sexual risk behaviors between IDUs and non-IDUs in St. Petersburg, Russia and assessed associations between substance use patterns and sexual risks within and between those two groups. Methods Cross-sectional survey data and biological test results from 331 IDUs and 65 non-IDUs who have IDU sex partners were analyzed. Multivariate regression was employed to calculate measures of associations. Results IDUs were less likely than non-IDUs to report multiple sexual partners and unprotected sex with casual partners. The quantity, frequency and intensity of alcohol use did not differ between IDUs and non-IDUs, but non-IDUs were more likely to engage in alcohol use categorized as risky per the alcohol use disorders identification test (AUDIT-C). Risky sexual practices were independently associated with monthly methamphetamine injection among IDUs and with risky alcohol use among non-IDUs. Having sex when high on alcohol or drugs was associated with unprotected sex only among IDUs. Conclusions Greater prevalence of sexual risk among non-IDUs who have IDU sex partners compared to IDUs suggests the potential for sexual transmission of HIV from the high-prevalence IDU population into the general population. HIV prevention programs among IDUs in St. Petersburg owe special attention to risky alcohol use among non-IDUs who have IDU sex partners and the propensity of IDUs to have sex when high on alcohol or drugs and forgo condoms.